The African American Challenge to Just War Theory - Cumming, R. author. aut Link
IX, 239 p.
Keywords: In this innovative treatment of the ethics of war, Ryan P. Cumming brings classical sources of just war theory into conversation with African American voices. The result is a new direction in just war thought that challenges dominant interpretations of just war theory by looking to the perspectives of those on the underside of history and politics.